Rekonstruksi Sanksi Pidana Korporasi dalam Tindak Pidana Lingkungan Hidup Berparadigma Green Victimology - Sindy Riani Putri Nurhasanah; Shane Evelina; Diah Ayu Ma'rifatul Jannah (Jurnal Hukum Lex Generalis, 2021)
This study aims to answer two questions, (1) What is the urgency of reconstructing corporate criminal sanctions in environmental crimes from the green victimology paradigm?; (2) How is the reconstruction of corporate criminal sanctions in environmental crimes with the paradigm of green victimology? To answer this question, the author conducted doctrinal research based on secondary data with qualitative analysis techniques. The research results showed that: (1) The urgency of the reconstruction of corporate criminal sanctions in environmental crimes is based on the absence of consistency in environmental-oriented sanctions,, so that criminal sanctions in the form of recovery do not run optimally. Based on the paradigm of green victimology, victims of environmental crimes are actually the environment. Therefore, criminal sanctions in the form of reparation need to be placed as the main choice; (2) Reconstruction of corporate criminal sanctions in environmental crimes with a green victimology paradigm can be carried out with several alternatives including making recovery the main criminal sanction or affirming the double-track system in the form of imposition of basic criminal sanctions and additional criminal sanctions, where additional criminal sanctions are imposed required is recovery. Meanwhile, if additional criminal sanctions in the form of recovery cannot be carried out, then additional criminal sanctions in the form of confiscation of assets or closure of business activities can be imposed as a substitute. The implementation of the recovery actions was supervised by the prosecutor by involving various stakeholders such as affected communities, environmentalists, and the Ministry of Environment and Forestry of the Republic of Indonesia.